Perforated Meckel's Diverticulitis in a Patient with Unknown Intestinal Malrotation: Clinical Pitfall - Burgard, Marie (Case Rep Surg, 2021)
Symptomatic Meckel's diverticulum is rare in adults. The most frequent complications are intestinal obstruction and diverticulitis. Diagnosis of Meckel's diverticulitis can be challenging due to nonspecific clinical manifestation of pain in the right lower abdominal quadrant, mimicking acute appendicitis. If associated with congenital malformation, such as intestinal malrotation, the anomalous anatomy makes the diagnosis even more challenging. In such cases, radiological imaging is essential to guide further management. We present a case of Meckel's diverticulitis in which physicians were initially misguided because of the atypical clinical presentation. Yet, anamnestic details directed to a potential underlying malformation, leading to supplementary radiological examination and the final diagnosis.